Religious Life in the Lives of School Dropout Adolescents: A Case Study in the Rambak Area - Azhari, Zima; Anwar, Muhammad Rofiq; Nurlaila, Nurlaila; Hapsoh, Siti (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to analyze the phenomenon of high school dropout rates among adolescents in the Rambak area, Jelitik Village, Sungailiat District, which coincides with their low religious awareness. Adolescents who drop out of school are often involved in negative behaviors such as unemployment, promiscuity, and a lack of religious practice. Although various religious activities are held in the community, the participation of adolescents in these activities remains limited. The purpose of this study is to describe the religious condition of school dropouts and to identify the factors that contribute to their decision to not continue their education. Using a qualitative descriptive approach, this study involved 8 school dropouts, their parents, religious leaders, and community members as informants. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, presentation, and conclusion techniques. The results of the study revealed that the religious dimensions of the school dropouts in Rambak consist of five aspects: ideological, ritualistic, experiential, intellectual, and consequential. Although they acknowledge religious teachings, their religious practices and knowledge remain low, and their religiosity does not significantly influence their behavior. The factors contributing to their decision to drop out of school include economic problems, lack of parental attention, low interest in education, and environmental influences.